RESULTS OF THE TRAWLING SURVEY BY AN INSTITUTIONAL BOAT CADALMIN II IN THE PALK BAY AND GULF OF MANNAR, MANDAPAM, DURING 1977-80 - Pillai, N Gopalakrishna; Dorairaj, K (Indian Journal of Fisheries, 2011)
During the course of trawling survey conducted in 1977-80 R.V.CADALMIN II (13.3 m, 100 BHP) landed from the Palk Bay and Gulf ofMannar a total ot 46,366 kg of 'all fisli" at an annual average catch rate of57.5 kg as a result of a total fishing effort of 806.3 h. Silverbellies formed 80%of the catch. The sub-areas 9-78|lF, 9-79|2B, 2C, 3B, 3C, 3D, 4A, 4B and 4Cwere found to be most productive. April-June in the Palk Bay and October-December in the Gulf of Mannar were the best seasons for trawling. Over 70%of the catch came from 4-10 m depth. When compared with earlier studies, achange was noticed in the composition of fish species in this region. The estimatedpotential yield for all the eight sub-areas surveyed in the Palk Bay andseven sub-areas in the Gulf of Mannar was 874.6 t and 473.7 t, respectively.